Enhanced electrical properties of lead-free BNLT-BZT ceramics by thermal treatment technique - Puripat Kantha (2018)
Electrical properties of lead-free solid solution ceramics from the Bi 0.4871 Na 0.4871 La 0.0172 TiO 3 (BNLT) and BaZr 0.05 Ti 0.95 O 3 (BZT) system have been improved by a thermal treatment technique. A modified two step mixed-oxide method was employed for the preparation of the (1-x)BNLT-xBZT ceramics, where x=0.06, 0.09, 0.12 and 0.20. After sintering at 1125 °C for 4 h, the BNLT-BZT ceramics were annealed at 825, 925 and 1025 °C. The annealing treatment caused an increase in dielectric constant of BNLT-BZT ceramics with x≤0.09 mol% and with x higher than 0.09 mol% the dielectric value dropped considerably. The ferroelectric properties of all annealed ceramic samples tend to decrease with increasing annealing temperature as confirmed by the slimmer P-E loops. The piezoelectric coefficient (d 33 ) increased with annealing temperatures and a maximum value of ∼170 pC/N was obtained from the ceramic samples annealed at 1025 °C with x=0.02. © 2012 Elsevier Ltd and Techna Group S.r.l.